(untitled) (Tanzania Medical Journal, 2023)
Background Deep vein thrombosis is a rare condition in the paediatric population, and it tends to overlap with musculoskeletal infections such as cellulitis, myositis or osteomyelitis. When associated with Staphylococcal infection, it is linked to poor prognosis. It should be strongly suspected in any child presenting with unilateral lower limb pain and swelling, limited mobility and fever. This is a case report of a pediatric patient who presented to our centre with deep vein thrombosis secondary to an underlying Staphylococcus aureus sepsis. Case presentation We present a case of a previously healthy seven-year-old boy, Chagga by tribe, who presented with a two-day history of right lower limb pain and swelling, which began eight days after falling from a tree. Three days later, the boy became weak and was unable to walk. He was initially admitted to the surgical ward, where abdominal visceral and limb trauma was ruled out. Clinically, he was ill-looking, tachypnoeic, tachycardic and febrile. The affected limb was swollen, tender, warm on touch and had limited range of motion at the hip and knee joints. Doppler ultrasound of the right leg revealed deep vein thrombosis of the distal femoral and popliteal veins, and blood culture revealed Staphylococcus aureus infection. Treatment was started in pediatric ICU, where, unfortunately, the boy’s condition continued to deteriorate, and three days later, the patient succumbed. Conclusion Deep vein thrombosis is relatively rare in the pediatric population. The occurrence has been shown to carry significantly high mortality if diagnosis and treatment are not done promptly. Staphylococcus aureus infection is very aggressive and has a unique propensity to cause venous thrombosis in association with cellulitis. The rapid evolution of septic emboli in DVT associated with Staphylococcal infection may complicate the management.